Misinformation and digital health literacy among American Indian and Alaska Native people - Marija Bogic; Juliana K Garcia; Erin Morgan; Ying-Chia Louise-Hsu; Amanda Boyd (Digital Health)
Background American Indian and Alaska Native (AI/AN) communities in the United States experience significant health disparities, compounded by socioeconomic challenges, systemic racism, limited health information access, and mistrust of health research, mainstream healthcare, and federal health organizations. Misinformation on digital media and variable digital health literacy further hinder informed decision-making. Objective Explore digital health literacy, digital technology use for health information-seeking, and the perceived influence of misinformation on health decision-making among AI/AN populations. Methods In 2022, 540 AI/AN individuals aged 18 and older were surveyed at two large cultural events. Cross-sectional data were collected on health decision-making, influence of misinformation on decisions, digital health literacy, and perceptions of misinformation on specific health topics. Paired t -tests examined differences in perceived effects of misinformation on health decisions. Results Although 62.7% of respondents felt confident evaluating online health information, only 35.5% used online information for health decisions. The perceived impact of misinformation on one's own health decisions was significantly lower for oneself (16.2%) than for friends and family (26.9%, p  < 0.001) or other AI/AN individuals (25.9%, p  < 0.001). Participants also believed AI/AN peoples were less vulnerable to misinformation than others (25.9 vs. 28.7%, p  < 0.001). Conclusions Addressing misinformation and digital barriers in AI/AN communities requires targeted public health initiatives. Strategies should focus on improving access to culturally relevant health information, integrating digital literacy education, and strengthening digital infrastructure with supportive policies. Collaborating with trusted community leaders can enhance culturally aligned health communication and information dissemination.